The National Democratic Revolution as an ideological instrument for transformation in South Africa. - Jankielsohn, Roy; Mollentze, Shelton (Eximia, 2021)
The National Democratic Revolution (NDR) with its key strategy of Democratic Centralism (cadre deployment strategy) remains the core ideological approach of South Africa’s governing party, the African National Congress (ANC), for the transformation of society and government. Both the NDR and democratic centralism are rooted in Leninist-Communism. The NDR as an ideology is used to mobilise political support, but also as the basis for all party political and government policy. The two phased approach of firstly taking control of government and secondly taking control of the rest of society depends on the employment of the cadre strategy. The cadre strategy has facilitated the deployment of party, and often factional, loyalists into positions of authority. This has had the unfortunate consequence of contributing to the massive abuse of party structures to enable state capture and large scale corruption. This article defines key theoretical concepts such as ideology and transformation, identifies the historical origins and conceptualises the NDR and explains democratic centralism as instrument for state capture. An explanation of the role of the NDR in the transformation of society is structured in terms of the various aspects identified in the definition of transformation, namely as a reaction to an unjust past, a new and better future (utopia), a social and political plan for fundamental and far-reaching change, planned (structured) political change and strategic political change. The article combines key theoretical concepts with historical and political realities to offer an academic explanation of current political considerations and challenges facing South Africa.